Nuclear envelope invaginations and cancer. - Malhas, A; Vaux, D (2014)
The nuclear envelope (NE) surrounds the nucleus and separates it from the cytoplasm. The NE is not a passive structural component, but rather contributes to various cellular processes such as genome organization, transcription, signaling, and stress responses. Although the NE is mostly a smooth surface, it also forms invaginations that can reach deep into the nucleoplasm and may even traverse the nucleus completely. Cancer cells are generally characterized by irregularities and invaginations of the NE that are of diagnostic and prognostic significance. In the current chapter, we describe the link between nuclear invaginations and irregularities with cancer and explore possible mechanistic roles they might have in tumorigenesis.